Spin-wave excitations in the spin-density wave state of doped iron pnictides. (4th September 2017) - Singh, Dheeraj Kumar
Abstract: We investigate spin-wave excitations in the spin-density wave state of doped iron pnictides within a five-orbital model. We find that the excitations along ( π, 0 )  →  ( π, π ) are very sensitive to dopings whereas they do not exhibit a similar sensitivity along ( 0, 0 )  →  ( π, 0 ). Secondly, the ellipticity of the elliptical ring-like excitations around ( π, 0 ) is also very much dependent on doping. Thirdly, the spin-wave spectral weight shifts towards the low-energy region as it moves away from zero doping. We find several features to be in qualitative agreement with the inelastic neutron-scattering measurements for the doped pnictides.